Analysis of binding properties of pathogens and toxins using multivalent glycan microarrays. Issue 27 (19th April 2018) - Kim, Hyoung Sub; Hyun, Ji Young; Park, Seong-Hyun; Shin, Injae
Abstract : Microarrays constructed by immobilizing free glycans on multivalent hydrazide-coated surfaces were applied to evaluate multivalent glycan binding properties of pathogens. Abstract : Pathogens infect hosts often through initial binding of their cell surface lectins to glycans expressed on the exterior of host cells. Thus, methods to evaluate the glycan-binding properties of pathogens are of great importance. Because of the multivalent nature of interactions of pathogens with glycans, the ability to assess the glycan density-dependent binding of pathogens is particularly important. In this study, we developed a facile technique to construct multivalent carbohydrate microarrays through immobilization of unmodified glycans on multivalent hydrazide-derivatized glass surfaces. This immobilization strategy does not require the use of multivalent glycoconjugates, which are typically prepared by using multistep sequences. The results of analysis of microarray images, obtained after incubation of multivalent glycan microarrays with cholera toxin B and pathogens such as uropathogenic E. coli and H. pylori, show that the binding affinities of toxins and pathogens for glycans are highly glycan density-dependent. Specifically, toxins and pathogens bind to glycans more strongly as the valency of the glycans on the microarrays is increased from 1 to 4. It is anticipated that the newly developed immobilization method will be applicable to the preparation of multivalent carbohydrate microarrays that are employed to evaluate multivalent glycan binding properties of a variety of pathogens and toxins.